Analysis of the Syar'u Man Qablana Theory and its Application in Sharia Financial Institutions - Royani; Moh. Asep Zakariya Ansori; Ending Solehudin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The purpose of this research is to study and deepen the analysis of the theory of sharu' man qablana and its application to Islamic Financial Institutions (LKS). Although syru' man qablana blasphemy is still being debated (mukhtalaf alaih), it is different from the Qur'an, sunnah, ijma and qiyas which are classified as agreed propositions (muttafaq fih). However, the theory of sharu' man qablana can be applied to Islamic Financial Institutions (LKS) today. As was done by Prophet Yusuf and Prophet Musa AS. The Shari'a under the Prophet Muhammad is a complement to the previous Shari'a. Therefore, it is necessary to conduct research on the concept of syar'u man qablana and its application in contemporary mu'âmalah maliyyah. This research is descriptive-analytic in nature which is classified as qualitative research, namely through library research by studying primary materials in the form of ushul fiqh books, especially those related to the concept of syar'u man qablana. The results of the study show that the application of Islamic law in the field of mu'âmalah maliyyah used to be kafalah contracts, ju'âlah contracts, ijârah contracts, and other contracts.